The relationship between body weight, dietary patterns, and menstruation duration and the incidence of anemia among female adolescents - Yuli Yuliana; Rita Ayu Yolandia; Hidayani Hidayani (THE JOURNAL OF Mother and Child Health Concerns, 2025)
Background: Anemia is a common health problem among female adolescents and may be influenced by several factors, including body weight, dietary patterns, and menstruation duration. Purpose: to determine the relationship between body weight, dietary patterns, and menstruation duration with the incidence of anemia among female adolescents Method: This was a quantitative study with a cross-sectional design. The population consisted of all female adolescents, with a total sample of 80 respondents selected using a total sampling technique. The independent variables were body weight, dietary patterns, and menstruation duration, while the dependent variable was anemia. Data was collected using a structured questionnaire and hemoglobin measurement with a digital method. Data analysis was performed using univariate and bivariate analyses with the Chi-Square test (α = 0.05). Results: The results showed that most respondents had normal body weight (46.25%), good dietary patterns (42.5%), normal menstruation duration (58.75%), and normal hemoglobin levels (48.75%). Bivariate analysis revealed significant relationships between body weight and anemia (p = 0.000), dietary patterns and anemia (p = 0.001), as well as menstruation duration and anemia (p = 0.003). Conclusion: Body weight, dietary patterns, and menstruation duration were significantly associated with the incidence of anemia among female adolescents. Suggestion: Teenagers are expected to maintain a healthy and balanced diet by paying attention to fulfilling their micronutrient intake.